Technology and Practice of Passwords: International Conference on Passwords, PASSWORDS'14, Trondheim, Norway, December 8-10, 2014, Revised Selected Papers - Mjolsnes, Stig F (LNCS sublibrary. SL 4, Security and cryptology, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Conference on Passwords, PASSWORDS 2014, held in Trondheim, Norway, in December 2014. The 8 revised full papers presented together with 2 revised short papers were carefully reviewed and selected from 30 initial submissions. The papers are organized in topical sections on hash functions, usability, analyses and new techniques.